Sustainable Iron-catalyzed direct imine formation by acceptorless dehydrogenative coupling of alcohols with amines - Jaiswal, Garima; Landge, Vinod Gokulkrishna; Jagadeesan, Dinesh; Balaraman, Ekambaram (Green Chemistry, 2016)
The Acceptorless Dehydrogenative Coupling (ADC) of alcohols with amines is reported using a heterogeneous Fe-catalyst. The reaction operates under mild conditions with the liberation of dihydrogen and water as the byproducts. The developed ADC strategy is simple, efficient, exhibits wide functional group tolerance and can be scaled up. The present catalytic approach possesses a dual role; acting as a catalyst as well as being magnetically separable. The sustainable reuse of a heterogeneous iron catalyst is also shown.